The effects of unified pooling arrangement on health inequity in China: a DID-RIF approach - Jing Wu; Yuqing Liu; Chuncheng Wang; Lianjie Liu; Jiaqian Lu (BMC Health Services Research)
Abstract Background To address the health inequity caused by decentralized management, China has introduced a provincial pooling system for urban employees’ basic medical insurance. This paper proposes a research framework to evaluate similar policies in different contexts. This paper adopts a mixed-methods approach to more comprehensively and precisely capture the causal effects of the policy. Ultimately, this paper aims to assess the impact of the UPA policy on health inequity. Methods This study takes the provincial unified reform of basic medical insurance for urban employees in China as an example, uses the China Family Panel Studies (CFPS) data and related policy documents, and adopts the DID-RIF hybrid method to test the impact of the equalization of the medical insurance system on health inequity, by using the interaction term in the DID (Difference-in-Differences) model as the independent variable in the RIF (Recentered Influence Function) to exclude the influence of other interfering variables. In addition, the DID method explores the effects of UPA on medical expenditures, which can guide the improvement of the policy. Results The empirical results show that the UPA policy increases the likelihood of patients developing chronic diseases within six months. Although factors such as age, gender, and marital status influence the probability of chronic disease, health inequity between income groups after the policy’s implementation primarily stems from the rise in outpatient and reimbursement expenses. Conclusions Although the gap in medical reimbursement expenses between participants of different socioeconomic statuses narrowed after the provincial medical insurance pooling reform, health inequity among the insured population increased. The equalized health insurance reform failed to address health inequities based on socioeconomic status. Additionally, the reverse reallocation of medical resources and outpatient arbitrage driven by moral hazard warrant close attention. This paper recommends that, in advancing the provincial pooling of UEBMI, greater focus should be placed on strengthening digital oversight and improving the hierarchical diagnosis and treatment system to promote social equity.